Preparation method of high-purity quartz sand

Through processing steps such as pre -processing, magnetic selection, floating, chloride and roasting, quenching and acid immersion, prepare high pure quartz sand, solve the problem of waste and environmental pollution of long stone powder resources during lithium -cloud mines, and realize high -purity quartz. Sand efficient preparation and sustainable resource.

CN119370853APending Publication Date: 2025-01-28宜丰国轩锂业有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411556468.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Feldspar powder produced during lithium mica ore dressing leads to waste of resources and environmental pollution, and it is difficult to effectively utilize and deal with the existing technology.

Method used

Through pre -processing, magnetic selection, floating, chloride and roasting, quenching and acid immersion process steps, high pure quartz sand is prepared to remove impurities in long stone powder and improve the purity of quartz.

Benefits of technology

Achieving the long stone powder in lithium cloud mother selection of lithium cloud mother, preparing high -purity quartz sand with SiO2 purity reaching more than 99.9%, avoiding waste of resources and environmental pollution. It has important environmental governance value and industrialized application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370853A_ABST
    Figure CN119370853A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of high-purity quartz sand, and relates to the technical field of mineral flotation. The preparation method of the high-purity quartz sand comprises the following steps: grinding and grading feldspar powder, then sequentially carrying out magnetic separation and flotation to obtain quartz concentrate, carrying out chloridizing roasting on the quartz concentrate, then carrying out quenching treatment to obtain activated quartz, carrying out acid leaching treatment on the activated quartz, filtering, and cleaning filter residues to obtain the high-purity quartz sand. According to the preparation method of the high-purity quartz sand, provided by the invention, the lepidolite mineral separation tailing feldspar powder can be fully and efficiently utilized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mineral flotation, and in particular to a method for preparing high-purity quartz sand. Background Art

[0002] In recent years, with the rapid development of the electric vehicle industry, my country's demand for lithium resources has continued to grow, prompting the rapid expansion of the lithium mica beneficiation industry. However, a large amount of feldspar powder will be produced during the lithium mica beneficiation process, which not only increases the storage pressure, but also because the feldspar powder contains a large amount of minerals with economic value, such as quartz, if not used, it will also lead to waste of resources and pollution to the environment. Therefore, how to deal with the feldspar powder produced by lithium extraction from lithium mica has become a problem that needs to be solved urgently by technicians in this field. Summary of the invention

[0003] 1. Technical issues to be solved

[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing high-purity quartz sand, which solves the technical problem of waste of resources and environmental pollution caused by the generation of feldspar powder during the lepidolite beneficiation process.

[0005] (II) Technical solution

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0007] The present invention provides a method for preparing high-purity quartz sand, comprising the following steps:

[0008] S1. Preprocessing

[0009] The feldspar powder produced after lithium extraction is pre-treated by grinding and classification, and passed through a 200-mesh screen; water and dispersant are added during the grinding process to fully disperse the feldspar powder;

[0010] S2, magnetic separation and impurity removal

[0011] The sieved feldspar powder samples are subjected to magnetic separation by magnetic separation process to remove magnetic impurity minerals such as hematite, ilmenite, etc.;

[0012] S3, flotation removal

[0013] Use a single tank flotation machine, add a regulator and then a collector to remove impurity minerals such as feldspar and kaolinite in the tailings, filter and dry to obtain quartz concentrate;

[0014] S4. Preparation of activated quartz

[0015] The quartz concentrate is placed in a muffle furnace for chlorination roasting, and then quenched to obtain activated quartz; chlorination roasting causes impurity elements (such as iron, aluminum, potassium, sodium, calcium, magnesium, titanium, etc.) to form volatile chlorides, which can significantly improve the purity of quartz.

[0016] S5, acid leaching and impurity removal

[0017] The activated quartz is treated with acid leaching, heated and stirred for leaching, filtered to achieve liquid-solid separation, the filter residue is repeatedly washed with pure water, and high-purity quartz sand is obtained after drying.

[0018] Preferably, the dispersant in S1 is selected from one or more of sodium hexametaphosphate, soluble starch, and ethylenediaminetetraacetic acid, and the added amount is 0.1-0.3% of the mass of the feldspar powder; after passing through the sieve, the mesh size of the feldspar powder is controlled at 40-200 meshes, and ultrasonic dispersion technology is used to improve the uniformity of the slurry to promote the subsequent magnetic separation effect.

[0019] Preferably, the magnetic separator in S2 is an electromagnetic high gradient magnetic separator with a magnetic field length of 1-1.5 T to ensure efficient removal of magnetic impurities (such as hematite, ilmenite, etc.) in the feldspar powder. Multiple repeated washing and multiple magnetic separations are used to ensure that the impurity content in the feldspar powder after magnetic separation is less than 1%.

[0020] Preferably, the one-coarse four-sweep reverse flotation process is adopted in S3, the pulp concentration is adjusted to 10-30%, the dosage of the adjusting agent is 2000-4500g / t, and at the same time, the pH value is maintained at 2-3.5, and the dosage of the collector is 4000-8000g / t. The flotation time is set to 2-5min, the stirring speed is 800-1500r / min, and the generation and dispersion of bubbles are monitored during the flotation process to optimize the flotation efficiency. After the flotation is completed, the bottom concentrate is repeatedly washed with pure water to remove impurities attached to the surface to ensure that the purity of SiO2 in the quartz concentrate reaches more than 98%.

[0021] Preferably, the regulator is RT719, and the use of the regulator does not require the addition of additional acid.

[0022] Preferably, the collector is RT351.

[0023] In the S4, a certain mass of quartz concentrate is weighed, uniformly mixed with chloride, and the mixture is placed in a high-purity corundum crucible for roasting. The roasting temperature is set to 700-1000° C. and the roasting time is 0.5-3 hours. During this period, the temperature change is monitored to ensure uniform roasting.

[0024] Preferably, the chloride is selected from one or more of ammonium chloride, potassium chloride, calcium chloride, sodium chloride, etc., and the added amount is 1-8% of the mass of quartz.

[0025] Preferably, the quenching treatment in S4 is to quickly pour the material in the crucible into a quenching device filled with pure water after the roasting is completed, so as to ensure that cracks are generated on the surface of the quartz concentrate during the rapid cooling process and impurities are exposed. After cooling, the precipitate is filtered to obtain activated quartz. The use of pure water for quenching and impurity removal has a simple process, low economic cost and wide adaptability.

[0026] In the acid leaching treatment in S5, the acid used is one or more of hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, phosphoric acid, oxalic acid, etc., and the specific concentration is adjusted according to the needs. The concentration of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid is 1-6mol / L, the concentration of hydrofluoric acid is 1-2.5mol / L, and the concentration of oxalic acid is 5-30g / L; the activated quartz and the prepared acid solution are placed in a polytetrafluoroethylene reactor, the liquid-solid ratio is controlled at 4-10:1, the reactor is placed in a water bath, the leaching temperature is set to 50-90°C, and the stirring speed is adjusted to 100-900r / min, and the reaction time is set to 2-8 hours. After cooling, the reaction solution is filtered and washed 5-10 times to ensure that impurities are fully removed, and finally a high-purity quartz sand with a SiO2 purity greater than 99.9% is obtained.

[0027] (III) Beneficial effects

[0028] The present invention provides a method for preparing high-purity quartz sand. Compared with the prior art, the method has the following beneficial effects:

[0029] 1. The preparation method of high-purity quartz sand provided by the present invention can fully and efficiently utilize the feldspar powder of lithium mica ore dressing tailings, avoiding the adverse effects of long-term accumulation of feldspar powder on company benefits and the environment, thereby establishing a good balance between resource recovery and environmental protection, and has important environmental governance value.

[0030] 2. The invention maintains the simplicity and economy of operation, with clear process steps and optimized operation flow, making it easy to realize large-scale industrial application; it provides a realistic and feasible technical path for the industrial production of high-purity quartz and promotes the industrialization process of comprehensive utilization of feldspar powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 It is a schematic diagram of the process flow of the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The embodiment of the present application solves the technical problem of how to extract high-purity quartz sand from feldspar powder by providing a method for preparing high-purity quartz sand.

[0035] The technical solution in the embodiment of the present application is to solve the above technical problems, and the overall idea is as follows:

[0036] In recent years, with the rapid development of the electric vehicle industry, my country's demand for lithium resources has continued to grow, prompting the rapid expansion of the lithium mica beneficiation industry. However, the large amount of feldspar powder produced not only increases storage pressure, but also leads to waste of resources and potential pollution to the environment. Therefore, the problem of handling feldspar powder produced by lithium extraction from lithium mica needs to be solved urgently. In addition, these tailings contain a large number of minerals with economic value, such as quartz; at the same time, the domestic demand for high-purity quartz is also increasing year by year. The preparation of high-purity quartz sand from feldspar powder can not only effectively solve the problem of large-scale accumulation and disposal of tailings, but also further improve the development and comprehensive utilization efficiency of lithium mica resources.

[0037] At present, the process of extracting high-purity quartz sand from feldspar powder is not mature, and there are few literature and patents on related technologies. Therefore, the feasibility of preparing high-purity quartz sand from feldspar powder is studied experimentally, and the realization of the process route of 99.9% high-purity quartz sand products is based on important research value and application prospects. This technological breakthrough not only helps to solve the problem of tailings accumulation, but also promotes the sustainable development of the lithium mica beneficiation industry.

[0038] The preparation method of the present invention comprises magnetic separation, flotation, chlorination roasting, quenching, acid leaching and other process methods. The magnetic separation and flotation processes are used to remove gangue mineral impurities in quartz. The acid leaching process removes quartz intergrowths and a small amount of inclusion impurities. Adding a proper amount of acid solution into the acid leaching solution can improve the purity of quartz sand. In addition, the crystal structure of quartz is changed by chlorination roasting, and combined with the quenching process, cracks are generated on the surface of the mineral, so that impurities are exposed, and inclusions and lattice impurities are removed, thereby obtaining high-purity quartz sand.

[0039] Therefore, the method of the present application can carry out fine treatment of different types of impurities in the beneficiation feldspar powder, such as gangue minerals, inclusions and lattice impurities, ensure the full removal of various impurities, significantly improve the purification effect, and provide reliable guarantee for the high purity of quartz sand; therefore, the high-purity quartz product prepared by the method of the present invention has a purity of more than 99.9%. This high-purity quartz sand can be used in high-tech manufacturing fields such as photovoltaic glass and silicon micropowder, has extremely broad application prospects and market demand, can provide high-quality basic materials for emerging industries, and has huge economic value and social benefits.

[0040] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0041] Example 1

[0042] This embodiment provides a method for preparing high-purity quartz sand. Figure 1 As shown, the following steps are included:

[0043] Take 500g of lithium mica feldspar ore, add 2L of water and 1g of sodium hexametaphosphate as a dispersant, grind in a ball mill until 90% pass through a 200-mesh sieve to obtain a feldspar sample with a suitable particle size; then use an electromagnetic high-gradient magnetic separator for magnetic separation, and set the magnetic field strength to 1.3T to remove magnetic impurities such as hematite and ilmenite in the feldspar; add the sample after magnetic separation to a single-slot flotation machine, adjust the pulp concentration to 20%, and use the adjuster RT719 to adjust the pulp pH value to 2.5. The flotation adopts a one-rough four-sweep reverse flotation process. First, in the roughing stage, add the adjuster RT719, the dosage of the agent is 2000g / t, and stir for 3 minutes to ensure that the agent fully interacts with the mineral surface; then add the collector RT351, the dosage of the collector is 2500g / t, and continue to stir for 3 minutes to complete the distribution of the agent, and finally, through aeration flotation, the feldspar concentrate is floated. The quartz concentrate obtained by roughing is further scavenged for 4 times to further improve the purity of the concentrate. In the first 3 scavengings, the dosage of the adjusting agent RT719 was controlled at 500g / t, and the dosage of the collector RT351 was 1250g / t. In the last scavenging, the dosage of the adjusting agent was reduced to 400g / t, and the dosage of the collector was 625g / t, further optimizing the balance between the reagent cost and the concentrate purity. After the scavenging is completed, the quartz concentrate obtained in the flotation tank is washed with pure water for multiple times to completely remove residual reagents and impurities. Subsequently, the washed quartz concentrate is filtered and dried at an appropriate temperature to finally obtain a high-quality quartz concentrate sample with a SiO2 purity of 98.31%. The impurity content of the quartz concentrate detected by ICP is as follows:

[0044]

[0045] Take 50g of quartz concentrate, mix it evenly with 1g of ammonium chloride, put it into a high-purity corundum crucible, place the crucible in a muffle furnace, set the roasting temperature to 900℃, and the roasting time is 2 hours; after the roasting is completed, quickly pour the material in the crucible into a container filled with pure water for quenching and cooling; after filtering, place the sample in a drying oven at 105℃ to dry, and obtain an activated quartz sample. Place 12g of the activated quartz sample in a polytetrafluoroethylene reaction vessel, add 60mL of the prepared 2mol / L hydrochloric acid solution, the liquid-solid ratio is 5:1, put the reaction vessel in a water bath, heat to 80℃, set the stirring speed to 150r / min, and the reaction time is 6 hours; after cooling, filter, wash the filter residue repeatedly with pure water 5 times, and finally dry to obtain high-purity quartz sand with a SiO2 purity of 98.47%. The impurity content of the quartz sand is as follows:

[0046]

[0047] Example 2

[0048] This embodiment provides a method for preparing high-purity quartz sand, comprising the following steps:

[0049] Take 800g of lithium mica ore dressing tailings sample, add 3L of water and 2g of sodium hexametaphosphate, grind in a ball mill until 90% passes through a 200-mesh sieve to obtain a tailings sample with suitable particle size; set the magnetic field strength to 1.5T, perform magnetic separation, and remove magnetic impurities such as hematite and ilmenite in the tailings; add the sample after magnetic separation to a single-slot flotation machine, adjust the pulp concentration to 20%, adopt a one-rough four-sweep reverse flotation process, and adjust the amount of collector on the basis of Example 1. The amount of collector RT351 in the roughing process is 3000g / t, the amount of collector RT351 in the first three sweeps is adjusted to 1000g / t, and the amount of the last sweep agent remains unchanged. After the scavenging is completed, the quartz concentrate obtained in the flotation tank is washed with pure water for multiple times to completely remove the residual reagents and impurities, filtered and dried to obtain a quartz concentrate with a SiO2 purity of 99.39%. The impurity content of the quartz concentrate detected by ICP is as follows:

[0050]

[0051] Take 50g of quartz concentrate, mix it evenly with 1g of ammonium chloride, put it into a high-purity corundum crucible, place the crucible in a muffle furnace, set the roasting temperature to 900℃, and the roasting time is 2 hours; after the roasting is completed, quickly pour the material in the crucible into a container filled with pure water for quenching and cooling; after filtering, place the sample in a drying oven at 105℃ to dry, and obtain an activated quartz sample. Place 12g of the activated quartz sample in a polytetrafluoroethylene reaction vessel, add 60mL of a prepared 2mol / L hydrochloric acid and 2mol / L hydrofluoric acid mixed acid solution, the liquid-solid ratio of the acid solution to the quartz concentrate is 5:1, place the reaction vessel in a water bath, heat to 80℃, set the stirring speed to 150r / min, and the reaction time is 6 hours; after cooling, filter, wash the filter residue repeatedly with pure water 5 times, and finally dry to obtain high-purity quartz sand with a SiO2 purity of 99.936%. The impurity content of the quartz sand is as follows:

[0052]

[0053] Example 3

[0054] This embodiment provides a method for preparing high-purity quartz sand, comprising the following steps:

[0055] Take 800g of lithium mica beneficiation tailings sample, add 3L of water and 2g of sodium hexametaphosphate, grind in a ball mill until 90% pass through a 200-mesh sieve, and obtain a tailings sample with suitable particle size; set the magnetic field strength to 1.5T, perform magnetic separation, and remove magnetic impurities such as hematite and ilmenite in the tailings; control the pulp concentration during flotation to 40%, and the flotation conditions are the same as in Example 1. After the scavenging is completed, the quartz concentrate obtained in the flotation tank is washed several times with pure water to thoroughly remove residual reagents and impurities, filtered and dried, and a quartz concentrate with a SiO2 purity of 99.31% is obtained. The impurity content of the quartz concentrate detected by ICP is as follows:

[0056]

[0057] Take 50g of quartz concentrate, mix it evenly with 1g of ammonium chloride, put it into a high-purity corundum crucible, place the crucible in a muffle furnace, set the roasting temperature to 900℃, and the roasting time is 2 hours; after the roasting is completed, quickly pour the material in the crucible into a container filled with pure water for quenching and cooling; after filtering, place the sample in a drying oven at 105℃ to dry, and obtain an activated quartz sample. Place 12g of the activated quartz sample in a polytetrafluoroethylene reaction vessel, add 60mL of a prepared 2mol / L nitric acid and 2mol / L hydrofluoric acid mixed acid solution, with a liquid-solid ratio of 5:1, place the reaction vessel in a water bath, heat to 80℃, set the stirring speed to 150r / min, and the reaction time is 6 hours; after cooling, filter, wash the filter residue repeatedly with pure water 5 times, and finally dry to obtain high-purity quartz sand with a SiO2 purity of 99.89%. The impurity content of the quartz sand is as follows:

[0058]

[0059] Comparative Example 1

[0060] The difference between this comparative example and Example 2 is that the chlorination roasting process is not included, that is, the quartz concentrate is only loaded into a high-purity corundum crucible, the crucible is placed in a muffle furnace, the roasting temperature is set to 900°C, and the roasting time is 2 hours; after the roasting is completed, the material in the crucible is quickly poured into a container filled with pure water for quenching and cooling, and the rest is the same as Example 2. High-purity quartz sand with a SiO2 purity of 85.906% is obtained.

[0061] Comparative Example 2

[0062] The difference between this comparative example and Example 2 is that the quenching process is not included, that is, the quartz concentrate is uniformly mixed with 1g of ammonium chloride, loaded into a high-purity corundum crucible, the crucible is placed in a muffle furnace, the roasting temperature is set to 900°C, and the roasting time is 2 hours; after the roasting is completed, the material in the crucible is only naturally cooled, and the rest is the same as Example 2. High-purity quartz sand with a SiO2 purity of 81.796% is obtained.

[0063] By comparing Example 2 with Comparative Examples 1-2, it can be seen that the high-purity quartz sand prepared in Example 2 has a higher purity. This is because the preparation method of Example 2 changes the crystal structure of quartz through chlorination roasting, and then combines the quenching process to cause cracks on the mineral surface. Under the synergistic effect of chlorination roasting and quenching process, impurities in the lattice are exposed and then removed, thereby obtaining higher purity quartz sand.

[0064] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0065] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing high-purity quartz sand, characterized in that: The preparation method comprises: grinding and classifying feldspar powder, and then sequentially performing magnetic separation and flotation to obtain quartz concentrate, performing chlorination roasting and quenching treatment on the quartz concentrate to obtain activated quartz, performing acid leaching treatment on the activated quartz, and then filtering and washing the filter residue to obtain high-purity quartz sand.

2. The method for preparing high-purity quartz sand according to claim 1, characterized in that: Water and dispersant are added during the grinding and classification process.

3. The method for preparing high-purity quartz sand according to claim 2, characterized in that: The dispersant is selected from one or more of sodium hexametaphosphate, soluble starch, and ethylenediaminetetraacetic acid, and the added amount is 0.1-0.3% of the mass of the feldspar powder.

4. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The magnetic field length used in the magnetic separation is 1-1.5T.

5. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The flotation adopts a one-roughing four-sweeping reverse flotation process, and a regulator and a collector are added to the ore pulp in sequence, and then filtered and dried to obtain quartz concentrate.

6. The method for preparing high-purity quartz sand according to claim 5, characterized in that: The slurry concentration is 10-30%, the pH value is 2-3.5, the ratio of the amount of the regulator to the mass of the slurry is 2000-4500g / t, the ratio of the amount of the collector to the mass of the slurry is 4000-8000g / t, the flotation time is 2-5min, and the stirring speed during flotation is 800-1500r / min.

7. The method for preparing high-purity quartz sand according to claim 5, characterized in that: At least one of the following conditions is met: The regulator is RT719; The collector is RT351.

8. The method for preparing high-purity quartz sand according to claim 1, characterized in that: At least one of the following conditions is met: The chloride used for chlorination roasting is selected from one or more of ammonium chloride, potassium chloride, calcium chloride and sodium chloride, and the addition amount is 1-8% of the mass of the quartz concentrate; The calcination temperature is 700-1000° C., and the calcination time is 0.5-3 hours.

9. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The quenching liquid is selected from pure water.

10. The method for preparing high-purity quartz sand according to claim 1, characterized in that: The acid used for the acid leaching treatment is selected from one or more of hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, phosphoric acid and oxalic acid.

Citation Information

Cited By

  • Alaite type high-purity quartz sand and directional impurity removal method thereof

    CN120172419A

  • Method for preparing quartz sand by efficiently separating potassium feldspar and quartz through hydrofluoric acid-free method

    CN121244361A